UNIVERSITY STARTUP INTENSITY AND FACULTY QUALITY. (22nd January 2019) - Showalter, Dean; Jensen, Richard
Abstract : Using a theoretical model of university technology transfer and licensing survey data from 1991 to 2013, we show that greater faculty quality and venture capital availability is positively associated with licenses to startups. We employ a two‐stage game of licensing terms (royalty rate and fixed fee) and development efforts to show that under reasonable conditions, licensing to a startup rather than an established firm will be more attractive to a technology transfer office (TTO) because the inventor's ownership share in a startup firm will increase total development efforts by the inventor and licensee. TTOs will be more likely to target startup licensees when the marginal effect of the faculty inventor's additional development effort on the probability of success is large relative to that of the venture capitalist or established firm. Empirical evidence supports the results of the model; using Associated University Technology Data licensing survey data and employing panel and cross‐sectional analyses, we show that an increase in the quality of engineering faculty has roughly twice the positive impact on startup licenses than on established firm licenses. Startup licensing is also strongly impacted by venture capital availability within institutions over time. ( JEL L24, L26, D86)